Spanish-speaking parents’ experiences after English-only and Spanish-only interactions with their children - Morales, Maria; Alfano, Alliete R.; Medina, Angela M. (Journal of Monolingual and Bilingual Speech, 2021)
The purpose of this study is to explore L1 versus L2 (or English-only versus Spanish-only) language use during play activities with their children from the perspective of the immigrant parent. Nine primarily Spanish-speaking parents of typically developing children 12–46 months of age were interviewed after completing play activities with their children in English and in Spanish. To develop participant language proficiency profiles, descriptive data were collected and analysed using clinical language tools. Data on participants’ perceptions of language were collected using semi-structured interviewing and analysed using thematic analysis procedures. Participant–child forced language interaction data were collected during play activities and analysed using linguistic analysis software. One major theme (forced English as a barrier to authentic communication) and three subthemes (child did not understand parent, parent felt uncomfortable and code-switching) were found based on their experiences. The results from this study show that these Spanish-speaking parents who are learning English feel more comfortable speaking to their children in their native language. The lack of comfort and proficiency in English had a negative impact on parents’ language output in quality and quantity which has implications for the children’s overall language exposure. The information obtained from this study may be used to educate professionals working with Spanish-speaking parents that are learning a second language.